If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(m + -1) + 4m = -8 + 9 + 4m Reorder the terms: -3(-1 + m) + 4m = -8 + 9 + 4m (-1 * -3 + m * -3) + 4m = -8 + 9 + 4m (3 + -3m) + 4m = -8 + 9 + 4m Combine like terms: -3m + 4m = 1m 3 + 1m = -8 + 9 + 4m Combine like terms: -8 + 9 = 1 3 + 1m = 1 + 4m Solving 3 + 1m = 1 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 3 + 1m + -4m = 1 + 4m + -4m Combine like terms: 1m + -4m = -3m 3 + -3m = 1 + 4m + -4m Combine like terms: 4m + -4m = 0 3 + -3m = 1 + 0 3 + -3m = 1 Add '-3' to each side of the equation. 3 + -3 + -3m = 1 + -3 Combine like terms: 3 + -3 = 0 0 + -3m = 1 + -3 -3m = 1 + -3 Combine like terms: 1 + -3 = -2 -3m = -2 Divide each side by '-3'. m = 0.6666666667 Simplifying m = 0.6666666667
| -17-2=3+4x+5 | | 3(4z-8)=12 | | 4(v-1)=-9v+9 | | 6z-3z+5-4=3z-5+4 | | -2(d+6)-3(4d-2)=22 | | 4x-8=11y-1 | | p=5/9*350000 | | -4(x-4)=28+8x | | 2g-12=16-10h | | 13.50/3 | | -45-5+2b=10 | | 175m-75m-53625=55000-175m | | -12x-3x=-8 | | Z=6x+px+2 | | 4x-45=7(x-9) | | -(4-6n)=n+11 | | B-1/2=b/3+7 | | ((7x+6)(2x+10))/((6x+2)(7x+5)) | | y=6/7x-2 | | -7+14k-13+-(-5k)+3= | | x/-8=-1-(-3) | | 3x=3(8-7x) | | 20.5=(w/3600)(703) | | 22-8x=-5(5x-1) | | -2(-3x+3y)=-2(-27) | | 3xy+3x=6 | | (11x)/6+2/3=2x | | 80x+2250=70x+5600 | | x+19+4x=-15-4x-20 | | 15x+7+19=100 | | 3(v-2)=7v-46 | | 117=r/29-(-115) |